Weight gain in Turner Syndrome: association to puberty induction? – longitudinal analysis of KIGS data. (18th March 2016) - Reinehr, Thomas; Lindberg, Anders; Toschke, Christina; Cara, Jose; Chrysis, Dionisis; Camacho‐Hübner, Cecilia
Summary: Context: Girls with Turner Syndrome (TS) treated or not treated with growth hormone (GH) are prone to overweight. Therefore, we hypothesize that puberty induction in TS is associated with weight gain. Methods: We analyzed weight changes (BMI‐SDS) between onset of GH treatment and near adult height (NAH) in 887 girls with TS enrolled in KIGS (Pfizer International Growth Database). Puberty was induced with estrogens in 646 (72·8%) girls with TS. Results: Weight status did not change significantly between GH treatment start and 1 year later (mean difference −0·02 BMI‐SDS), but increased significantly ( P < 0·001) until NAH (+0·40 BMI‐SDS). The BMI‐SDS increased +0·21 until start of puberty ( P < 0·001). Girls with spontaneous and induced puberty showed similar BMI‐SDS changes. Puberty induction at ≥12 years was associated with a significant ( P < 0·001) less increase of BMI‐SDS (+0·7 BMI‐SDS) between baseline and NAH compared to puberty induction at <12 year (+1·0 BMI‐SDS). In multiple linear regression analyses changes of BMI‐SDS between baseline and NAH were negatively associated with baseline BMI‐SDS ( P < 0·001), GH doses ( P = 0·015), and age at puberty induction ( P < 0·001), positively with years on GH treatment ( P = 0·004), while duration and dose of estrogens, its route of administration (transdermal/oral), changes of height‐SDS, thyroxin and oxandrolone treatment, and karyotype did not correlate significantly to changes of BMI‐SDS in this time period. Conclusions: Puberty does not seem to play a major role in weight gain in girls with TS since the majority of the increases in BMI‐SDS occurred before puberty. However, late puberty induction seems to decrease the risk of weight gain.